2009
DOI: 10.1016/j.elspec.2009.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Relative electron inelastic mean free paths for diamond and graphite at 8keV and intrinsic contributions to the energy-loss

Abstract: a b s t r a c tWe used hard X-ray photoelectron spectroscopy (HAXPES) with 8 keV X-rays to investigate the 1s emission of carbon. We recorded spectra extending from the peak of the C 1s electrons ("elastic" line) to electrons with up to 110 eV energy-loss. Using two samples side by side, we could compare the inelastic mean free paths (IMFPs) of the electrons of almost 8 keV in diamond and graphite and find them to be practically identical despite about 50% difference in densities. Published extrapolations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…We searched for but did not find any correlation between the RMS deviations in Table 6 and the sum‐rule errors in Table 3. We also note that our calculated IMFPs for diamond are consistent with IMFPs determined from elastic‐peak electron‐spectroscopy (EPES) experiments by Zemek et al 44 and the IMFP calculations of Rehr et al 45 while our IMFPs for Cs are consistent with those calculated by Rehr et al 45 In addition, Kunz et al 46 analyzed XPS spectra of diamond and graphite that were obtained with 8 keV X‐rays and found that the ratio of the IMFPs of diamond and graphite was 0.95 (for an electron energy of 7 716 eV). This ratio is slightly larger than the corresponding ratio of our calculated IMFPs of 0.88.…”
Section: Imfp Resultssupporting
confidence: 90%
“…We searched for but did not find any correlation between the RMS deviations in Table 6 and the sum‐rule errors in Table 3. We also note that our calculated IMFPs for diamond are consistent with IMFPs determined from elastic‐peak electron‐spectroscopy (EPES) experiments by Zemek et al 44 and the IMFP calculations of Rehr et al 45 while our IMFPs for Cs are consistent with those calculated by Rehr et al 45 In addition, Kunz et al 46 analyzed XPS spectra of diamond and graphite that were obtained with 8 keV X‐rays and found that the ratio of the IMFPs of diamond and graphite was 0.95 (for an electron energy of 7 716 eV). This ratio is slightly larger than the corresponding ratio of our calculated IMFPs of 0.88.…”
Section: Imfp Resultssupporting
confidence: 90%
“…It is clear, however, that the area of the tail is at least half the area of the main component. In comparison, the intrinsic intensity for high-energy photoemission of carbon was found to be 58% of the total intensity [25] very similar to the value found here. In the context of medical physics, these 'shake' electrons are important as they could provide a significant source of additional low-energy electrons with their large genotoxic effects [26].…”
Section: High-energy Conversion Electron Spectrasupporting
confidence: 88%
“…High photoelectron kinetic energy by hard X-ray excitation causes larger IMFP compared to experiments using the soft X-ray. For example, IMFP of graphite C 1s photoelectron at photon energy of 8 keV is estimated to be 9.61 nm [58]. The large IMFP is advantageous for measurements of buried interfaces, such as solidliquid and solid-solid interfaces [59,60], and thus AP-HAXPES has been applied for in-situ measurements of operating devices, such as a fuel cell [61] and a photoelectrochemical cell [62].…”
Section: Ambient-pressure X-ray Photoelectron Spec-troscopymentioning
confidence: 99%